REGULASI PELAKSANAAN VERIFIKASI PENELUSURAN TEKNIS IMPOR OLEH LEMBAGA SURVEYOR DI KAWASAN PABEAN NEGARA MUAT BARANG (PRE-BORDER AREA): Regulation on The Implementation of Technical Import Verification by Surveyor Agencies in The Pre – Border Area - Febianti , Dianing Paramita (Fakultas Hukum, Universitas Trisakti, 2025)
This study discusses the regulations regarding the implementation of Technical Import Verification (VPTI) by Surveyor Agencies in customs areas of the country where goods are loaded, also known as the pre-border area. Findings of non-compliance in imported goods outside the customs area (post-border) indicate gaps in supervision, which impact the integrity of import data, supply chain security, and consumer safety and protection. This article highlights the functions and duties of a Surveyor Agency in the pre-border area, as well as the regulations and operational standards applied by the Agency in carrying out VPTI tasks. Using a legislative approach, this paper explores the process flow of VPTI implementation and the role of the Surveyor Agency within the customs area of the country where goods are loaded.